Mathematical methods for finance tools for asset and risk management - Focardi, Sergio M.; Fabozzi, Frank J.; Bali, Turan G. (The Frank J. Fabozzi series, 2013)
The mathematical and statistical tools needed in the rapidly growing quantitative finance field With the rapid growth in quantitative finance, practitioners must achieve a high level of proficiency in math and statistics. Mathematical Methods and Statistical Tools for Finance, part of the Frank J.